2020
DOI: 10.1155/2020/3856242
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Lowering Treatment and Eligibility for PCSK9 Inhibition in Post-Myocardial Infarction Patients in Italy: Insights from Two Contemporary Nationwide Registries

Abstract: Introduction. The current use of lipid lowering therapies and the eligibility for proprotein convertase subtilisin/kexin-9 (PCSK9) inhibitors of patients surviving a myocardial infarction (MI) is poorly known. Methods. Using the data from two contemporary, nationwide, prospective, real-world registries of patients with stable coronary artery disease, we sought to describe the lipid lowering therapies prescribed by cardiologists in patients with a prior MI and the resulting eligibility for PCSK9 inhibitors acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…PPI network construction unravelled 9 seed genes using NTA. On the other hand, by reanalyzing GSE59867, the results demonstrated that immune system responses, especially innate immune response, were activated in STEMI patients compared to stable CAD patients, which may be due to the lipid accumulation and further deterioration of coronary vessel status [21][22][23]. The status can be partly reversed by β-blockers not calcium antagonists [24].…”
Section: Discussionmentioning
confidence: 99%
“…PPI network construction unravelled 9 seed genes using NTA. On the other hand, by reanalyzing GSE59867, the results demonstrated that immune system responses, especially innate immune response, were activated in STEMI patients compared to stable CAD patients, which may be due to the lipid accumulation and further deterioration of coronary vessel status [21][22][23]. The status can be partly reversed by β-blockers not calcium antagonists [24].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have documents that PCSK9 inhibitors could be used for treating hypercholesterolemia conditions. 13,[61][62][63] Besides, loss-of-function mutations in the PCSK9 gene reduce LDL levels and safety in cardiovascular disease cases. 26,46,64 In addition to its effect on lipoprotein synthetic procedure and its pro atherosclerotic property, PCSK9 acts as a mediator in glucose metabolism, weight complications and so on.…”
Section: Clinical Significancementioning
confidence: 99%
“…53 Another analysis considered PCSK-9 eligibility according to the ESC / EAS and Agenzia Italiana del Farmaco (AIFA) regulatory agency criteria using data from 2 Italian, nationwide, prospective, real -world registries of patients with stable coronary artery disease. 54 Similar to the ACC, the AIFA criteria consider post -MI patients eligible for PCSK-9 inhibitor use if they show LDL -C levels higher than 100 mg/dl despite treatment with high -potency statins + ezetimibe, or ezetimibe alone in the presence of well -documented statin intolerance. Despite the ESC / EAS guideline recommendations to lower LDL -C levels in post -MI patients to a target level below 70 mg/dl using high -intensity statin therapy in combination with ezetimibe, if needed, the analysis revealed that numerous patients were undertreated with conventional lipid -lowering therapies.…”
Section: Prescription Barriers and Possible Solutionsmentioning
confidence: 99%
“…Despite the ESC / EAS guideline recommendations to lower LDL -C levels in post -MI patients to a target level below 70 mg/dl using high -intensity statin therapy in combination with ezetimibe, if needed, the analysis revealed that numerous patients were undertreated with conventional lipid -lowering therapies. 54 A low -dose statin was prescribed in 9.3% of patients, and a high dose, in 61.4%; statin + ezetimibe therapy was used in less than 18% of cases. In the 3074 post--MI patients with LDL -C data available, a target level below 70 mg/dl was achieved in only 1186 patients (38.6%), and around a quarter (24%) presented a LDL -C level higher than or equal to 100 mg/dl.…”
Section: Prescription Barriers and Possible Solutionsmentioning
confidence: 99%
See 1 more Smart Citation